Second-step lectotypification of Garcinia stipulata (Clusiaceae) and its recollection from Darjeeling-Sikkim Himalaya, India - Ranjan, Vinay; Kumar, Anant; Krishna, Gopal (Phytotaxa, 2022)
Garcinia stipulata (Clusiaceae) is recollected after a lapse of 53 years from Neora Valley National Park, Darjeeling, India. A taxonomic description with photograph and illustration are provided to facilitate easy identification. Also, a second-step lectotypification is discussed.